2014
DOI: 10.1161/circinterventions.113.001098
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes of Mitral Valve Geometry During Interventional Edge-to-Edge Repair With the MitraClip System Are Associated With Midterm Outcomes in Patients With Functional Valve Disease

Abstract: Background-Transcatheter mitral valve repair (TMVR) is a treatment option in patients with symptomatic functional or degenerative mitral regurgitation (DMR) at high surgical risk. The acute effect of MitraClip procedure on mitral valve (MV) annular geometry and its relation to functional outcomes is unclear. We sought to assess immediate effect of TMVR on MV annular geometry with 3-dimensional (3D) transesophageal echocardiography and the association of MV diameter reduction with functional response after 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 23 publications
(28 reference statements)
5
33
3
1
Order By: Relevance
“…In a previous study, it has been shown that reduction in AP diameter was not statistically significant in functional MR group. 16 On the other hand, Schueler et al 17 circumference is about 100 mm, 19 and the mean pre-clip annular circumference for all of our patients was about 130 mm, slightly larger for the degenerative group and slightly smaller for the functional group ( Figure 2). All patients had some degree of annular dilation (considering the upper limit of normal at 107 mm).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In a previous study, it has been shown that reduction in AP diameter was not statistically significant in functional MR group. 16 On the other hand, Schueler et al 17 circumference is about 100 mm, 19 and the mean pre-clip annular circumference for all of our patients was about 130 mm, slightly larger for the degenerative group and slightly smaller for the functional group ( Figure 2). All patients had some degree of annular dilation (considering the upper limit of normal at 107 mm).…”
Section: Discussionmentioning
confidence: 45%
“…In a previous study, it has been shown that reduction in AP diameter was not statistically significant in functional MR group . On the other hand, Schueler et al has reported significant changes in all diameters with the exception of the bicommissural diameter in functional MR stating a positive clinical course. The same study revealed no difference in the degenerative group.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the catheterization laboratory, 3D TEE can assist the positioning of the clip on the MV orifice, grasping of both MV leaflets, and evaluating the result, including visualization of the residual MR (Fig. 5) [60,61,62,63]. At the author's institution, 3D TEE is indispensable for the success of this procedure.…”
Section: Mitral Regurgitationmentioning
confidence: 99%
“…In terms of mechanism, the mitral clip might prove useful in functional MR by targeting the distorted annulus associated with this condition. In fact, the mitral clip has been shown to reduce mitral annular dimensions in functional MR, and this is associated with clinical improvement(12…”
mentioning
confidence: 99%